2010
DOI: 10.1001/archoto.2010.195
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptors in Regulatory T Cells of Patients With Head and Neck Cancer<alt-title>TLRs in T-reg Cells of HNSCC Patients</alt-title>

Abstract: Objective: To investigate the role of Toll-like receptor (TLR) signaling and T-regulatory (T-reg) cells in patients with head and neck squamous cell carcinoma (HNSCC).Design: Multicolor flow cytometry was used to study the frequency and phenotype of CD4 Patients: Eleven patients with HNSCC and 10 healthy donors (HDs) were studied. T-reg and T-eff cells were isolated from PBMCs using a magnetic bead-activated cell-sorting technique.Main Outcome Measures: Proliferation of T-eff cells and suppressor activity of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
1
16
2
Order By: Relevance
“…This is in contrast to the majority of results reported by previous HNSCC studies where Tregs have been found to be increased in the cancer patients [10,22,30,31]. However, not all cancer publications report an elevated trend, with some observing no significant difference in the frequency of Tregs in the peripheral circulation of patients and healthy donors, including one study examining oral SCC [32,33].…”
Section: Discussioncontrasting
confidence: 73%
“…This is in contrast to the majority of results reported by previous HNSCC studies where Tregs have been found to be increased in the cancer patients [10,22,30,31]. However, not all cancer publications report an elevated trend, with some observing no significant difference in the frequency of Tregs in the peripheral circulation of patients and healthy donors, including one study examining oral SCC [32,33].…”
Section: Discussioncontrasting
confidence: 73%
“…A short exposure of Treg to cisplatin prior to activation appears to protect them from AICD and is mediated by elevated expression levels of survival proteins, Bcl-2 and Bcl-xL, and lower levels of pro-apoptotic Bax than those observed in T conv (Figure 5). Still another possibility is that toll like receptors (TLR) present on Treg (32) and signaling in response to ligands released by radiation-induced tissue damage activate the PI3K/Akt survival pathway, protecting Treg from effects of CRT. Such TLR-mediated chemoresistance has been previously described for tumor cells (3335).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that autophagy defects may increase oxidized HMGB1. Tregs, especially in cancer patients, express both HMGB1-recognizing receptors TLR4 and RAGE [190]. HMGB1 increased secretion of IL-10 and the suppressive capacity in Tregs in a RAGE-dependent manner.…”
Section: Regulatory T Cellsmentioning
confidence: 99%